Survival analysis with applications to Ga-Dikgale children - Makgaba, Mokgoporo Enoch Walace (My University, 2014)
The health and survival of children are important measures of the social wellbeing and health status of the community. The World Community made a commitment to reduce under-five mortality by two-thirds between 1990 and 2015. The purpose of this study was to identify factors that have influence on child survival. The Dikgale Health and Demographic Surveillance System (HDSS) data for children born between 01 January 1996 and 31 December 2010 were analysed using cross-tabulation, logistic regression and survival analysis to determine factors that have influence on child survival. The findings revealed that mother’s survival status and child birth weight are significantly associated with child survival. The results showed that the odds that children born to mothers who are alive survive beyond five years are almost four times the odds that children born to mothers who are not alive survive beyond five years. The study also found that the odds that children born with birth weight 2.5kg or more survive beyond five years are almost two times that of children born with birth weight less than 2.5kg. The results of this study may help in formulating strategies and interventions that improve the lifespan of children and assist in the reduction of child mortality. KEY CONCEPTS Child survival, Health Demographic Surveillance System, Cross-tabulation, Logistic regression, Survival analysis, Mother’s survival status, Birth weight.
Thesis (M.Sc. (Statistics)) -- University of Limpopo, 2014
Keywords: Child survival.; Child mortality.; Children -- Mortality.; Child health services.; Community health care services for children -- South Africa -- Limpopo.; Primary health care.